2022
DOI: 10.1002/jsfa.11953
|View full text |Cite
|
Sign up to set email alerts
|

Flavoring of sea salt with Mediterranean aromatic plants affects salty taste perception

Abstract: BACKGROUND: Salt (sodium chloride) is an essential component of daily food, crucial for many physiological processes. Due to health risks related to salt over consumption, considerable interest is devoted to strategies to reduce dietary salt intake. In this work we evaluated the sensory dimensions of sea salts flavored with Mediterranean aromatic plants with the aim to confirm the role of herbs/spices in the enhancement of salty perception and to validate the use of flavored salts as a strategy to reduce salt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(41 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…Gao and Colleagues suggested the use of Chinese douche, a traditional fermented soya bean product, to improve salty taste and reduce the salt intake [ 10 ]. In our previous study [ 3 ], we confirmed the important role of Mediterranean aromatic plants (rosemary, myrtle, orange, and saffron) in the enhancement of salt perception and qualified the use of flavored sea salts as a potential strategy to reduce daily salt intake.…”
Section: Introductionsupporting
confidence: 75%
See 4 more Smart Citations
“…Gao and Colleagues suggested the use of Chinese douche, a traditional fermented soya bean product, to improve salty taste and reduce the salt intake [ 10 ]. In our previous study [ 3 ], we confirmed the important role of Mediterranean aromatic plants (rosemary, myrtle, orange, and saffron) in the enhancement of salt perception and qualified the use of flavored sea salts as a potential strategy to reduce daily salt intake.…”
Section: Introductionsupporting
confidence: 75%
“…The semi-industrial production of flavored salts was carried out as previously reported [ 3 , 27 ]. Table 1 indicates the composition per 100 g of product of FS, as indicated on the commercial labels.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations